Persepsi Mahasiswa Terhadap Perkuliahan Daring Di Masa Pandemi Covid 19 - Muhammad Akbar Syafruddin; Ikadarny Ikadarny; Andi Sahrul Jahrir (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The aim of the study was to determine the physical education students’ perception  about online classes during the Covid-19 pandemic. The method used in this study is descriptive quantitative to determine students' views on sports, health and entertainment STKIP YPUP Makassar. The data collection technique used multimedia questionnaires distributed using Google Forms. The sample of random sampling techniques used in this study were 35 students. The results of this study showed that 29 students or 83% agree, 1 student or 3% strongly agree, 2 students or 6% disagree and 3 students or the 8% disagree to apply for online classes during this period 2019 Coronavirus pandemic. Therefore, it can be concluded that the students agreed to implementation of online classes during the Covid-19 pandemic